Spectrum of genetic variants in bilateral sensorineural hearing loss - Ali, Amanat; Tabouni, Mohammed; Kizhakkedath, Praseetha; Baydoun, Ibrahim; Allam, Mushal; John, Anne; Busafared, Faiza; Alnuaimi, Ayesha; Al-Jasmi, Fatma; Alblooshi, Hiba (Frontiers in Genetics, 2024)
Background: Hearing loss (HL) is an impairment of auditory function with identified genetic forms that can be syndromic (30%) or non-syndromic (70%). HL is genetically heterogeneous, with more than 1000 variants across 150 causative genes identified to date. The genetic diagnostic rate varies significantly depending on the population being tested. Countries with a considerably high rate of consanguinity provide a unique resource for studying rare forms of recessive HL. In this study, we identified genetic variants associated with bilateral sensorineural HL (SNHL) using whole-exome sequencing (WES) in 11 families residing in the United Arab Emirates (UAE). Results: We established the molecular diagnosis in 6 probands, with 6 different pathogenic or likely pathogenic variants in the genes MYO15A, SLC26A4 and GJB2. One novel nonsense variant, MYO15A:p.Tyr1962Ter*, was identified in a homozygous state in one family, which has not been reported in any public database. SLC26A4 and GJB2 were found to be the most frequently associated genes in this study. In addition, 6 variants of uncertain significance (VUS) were detected in 5 probands in the genes CDH23, COL11A1, ADGRV1, NLRP3, and GDF6. In total, 12 variants were observed in 8 genes. Among these variants, eight missense variants (66.7%), three nonsense (25.0%), and one frameshift (8.3%) were identified. The overall diagnostic rate of this study was 54.5%. About 45.5% of the patients in this study came from consanguineous families. Conclusions: Understanding the genetic basis of HL provides insight for the clinical diagnosis of hearing impairment cases through the utilization of next-generation sequencing (NGS). Our findings contribute to the knowledge of the heterogeneous genetic profile of HL, especially in a population with a high rate of consanguineous marriage in the Arab population.